Political autonomy of women in Colombia and Argentina : an analysis of human rights and public policies - Mora Cuervo, Ruth Astrid (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The vindication of women's political rights has been a constant struggle for their autonomy and gender equality, acquired in international consensus on human rights and materialized in public policies. The objective of this article is to analyze the guarantee of human rights that the public policies of gender equity / equality in Colombia and Argentina achieved to achieve the empowerment and political autonomy of women. This is achieved under a qualitative, documentary and multiple case study approach. Under a normative evaluation approach and content analysis of public policies, it is analyzed how the public policies of the countries analyzed use most of the minimum content established in the Regional Gender Agenda to achieve political autonomy for women. The foregoing contrasts with the figures of political inequality that exist in Argentina and Colombia both in participation and access to positions of power. These results show the need to periodically evaluate the inclusion of the minimum content of rights established in international commitments in the formulation and implementation of public policies.